2019
DOI: 10.1111/mmi.14274
|View full text |Cite
|
Sign up to set email alerts
|

The carbon catabolite repressor CcpA mediates optimal competence development in Streptococcus oligofermentans through post‐transcriptional regulation

Abstract: Natural transformation increases the genetic diversity of bacteria, but is costly and must be strictly controlled. We previously found that deletion of ccpA, a key regulator of carbon catabolite repression (CCR), reduced transformation efficiency of Streptococcus oligofermentans, the current work further investigated the regulatory mechanisms of CcpA. The competence operon comCDE is subjected to basal and autoregulatory transcription. A luciferase reporter detected a transcriptional readthrough (TRT) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…This suggests that CcpA could have a role in transcription termination or regulates the stability of these RNAs. Consistent with the former, Streptococcus oligofermentans CcpA binds tRNA Arg in vitro and deletion of ccpA resulted in modest transcriptional readthrough of tRNA Arg 45 . This points towards a role for CcpA in transcription termination.…”
Section: Discussionsupporting
confidence: 60%
“…This suggests that CcpA could have a role in transcription termination or regulates the stability of these RNAs. Consistent with the former, Streptococcus oligofermentans CcpA binds tRNA Arg in vitro and deletion of ccpA resulted in modest transcriptional readthrough of tRNA Arg 45 . This points towards a role for CcpA in transcription termination.…”
Section: Discussionsupporting
confidence: 60%
“…Another example is catabolite control protein A (ccpA), a regulatory metabolic protein that directs selective metabolism of available sugars and has been found to play a role in competence in two Mitis group streptococci: S. cristatus and S. gordonii [61,62]. Transcriptome analysis of S. gordonii during competence revealed that ccpA was downregulated during the competence state, while a similar observation was made with S. sinensis Forsyth1A (Table 5) [23].…”
Section: Resultsmentioning
confidence: 78%
“…Researchers had previously found that CcpA indirectly aids in the regulation of early competence genes, including comCDE, in Mitis group streptococci [62,76]. For example, it was found that an S. oligofermentans ΔccpA mutant had higher expression levels of phosphorylated ComE, which is known to bear great influence on other competence genes, such as comX [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5′ and 3′ RACEs were performed as described previously ( 57 ) with slight modifications. Briefly, So-RNaseZ-digested products of tRNA precursor transcripts were purified on 10% urea-PAGE gels using a ZR small-RNA PAGE recovery kit (Zymo Research, Irvine, CA, USA), and then the 5′ and 3′ ends were ligated with 50 pmol of universal microRNA (miRNA)-cloning linker 5′-CAGACUGGAUCCGUCCUC-App-3′ and 5′-AppCUGUAGGCACCAUCAAU-ddC-3′ (synthesized by Integrated DNA, Coralville, IA, USA), respectively, with the addition of 20 U of T4 RNA ligase (Ambion, Austin, TX, USA) in the presence of 40 U of RNasin-Plus.…”
Section: Methodsmentioning
confidence: 99%